Maternal mortality Maternal Perinatal Institute in the period 1991-1995 - Torres, Juan (2015)
OBJECTIVE: To determine recent maternal mortality rate at Maternal and Perinatal Institute, study its characteristics and compare it with the previous five year period. DESIGN: Simple descriptive retrospective study of all cases of maternal death (73) at Maternal and Perinatal Institute between 1991 and 1995. RESULTS: Maternal mortality rate was 62,9 per 100000 living newborns. First cause of death was septic abortion (23,3%). Second were hipertensive diseases with 13 cases (17,8%). Third were hemorrhages (16,4%). Indirect obstetrical causes (21,9%) have 9,6% of tuberculosis. Forty-six patients died before 48 hours of hospitalization (63%). CONCLUSIONS: Maternal mortality rate has slighty decreased in comparison with the previous 5-year period, with figures of 35,8% and 48,3% per 100000 l.n. respectively in 1994 and 1995. Over half of cases are preventable deaths and corrective measures have to be taken.